An analytical model for performance prediction and optimization of thermoelectric generators with varied leg cross-sections. (August 2021) - Wang, Pan; Wang, Baolin; Wang, Kaifa; Gao, Ruxin; Xi, Li
Highlights: The generated electric potential difference is independent with the leg shapes. The key to maximum output power is to minimize the leg resistance. Increasing the leg volume may significantly enhance the TEG performance. Abstract: With the improvement on materials performance gradually reaching its bottleneck, more and more works focus on optimizing the device structures to seek further performance enhancement of thermoelectric (TE) devices. This paper proposed an analytical model to calculate the performance of thermoelectric generators (TEGs) with varied leg cross-sections considering temperature-dependent material properties. The explicit expressions of output power and efficiency are derived and the model is verified by finite element method (FEM). Furthermore, the optimization of leg geometry for higher device performance is performed based on the presented model, the results show that the key to maximum output power is to minimize the leg resistance; and increasing the leg volume may simultaneously raise the output power and efficiency. In addition, we apply the presented model to optimize the leg shape of a commercial TEG module and find that the optimized geometry can simultaneously achieve an enhancement up to 43.1% for output power and 9.67% for efficiency. The presented model thus may be useful in designing high-performance TEGs and shed considerable light on the principles of TEG design.